Employee voice as a behavioural response to psychological contract breach: The moderating effect of leadership style - Larysa Botha; Renier Steyn (Cogent Business & Management, 2023)
Empirical evidence shows that psychological contract breach (PCB) leads to negative work behaviours of employees, including withholding of discretionary activities such as employee voice (EV). This research aims to determine empirically how PCBs are linked to different types of EV, and how different leadership styles affect these relationships. The paucity of literature on the relationship between all three variables necessitated this research. The study targeted medium to large South African organisations with more than 60 employees. The population sample was representative of a broad range of South African employees. This research adopted a crosssectional survey design, whereby the respondents were asked to answer a questionnaire about PCB, leadership styles and EV. Correlation analyses were used to test the direct links between variables and regression analyses to test for the moderation effect of leadership styles on the PCB-EV link. The data were collected from 620 respondents from 11 organisations. All the instruments showed acceptable psychometric properties. Three findings were dominant: PCB correlated negatively with promotive types of EV and positively with prohibitive types of EV; leadership styles were a weaker predictor of EV than PCB; and the PCB-EV relationship was, in most cases, partially moderated by leadership styles. PCB and leadership styles influence EV; however, leadership styles only partially influence the PCB-EV relationship. Applying a specific leadership style to influence EV under conditions of PCB is partially effective. Managers should circumvent PCB and focus on the fulfilment of PC, as this would elicit promotive EV and lessen prohibitive EV.
Keywords: 650; moderation; constructive voice; defensive voice; destructive voice; leadership styles; Psychological contract breach; supportive voice